(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Breast, cervical, and colorectal cancer screening are evidence-based interventions recommended by most governmental agencies and scientific societies. The aim of this review is to assess the quality of guidelines on screening and to describe differences according to the context in which they were produced. Methods: A literature search of the main databases, websites on health care, and guidelines, as well as the websites of several scientific societies was carried out in order to identify the most recent guidelines (since 2000) on cervical, breast, and colorectal cancer screening. Only documents written in Italian or English were included. Two investigators independently assessed quality by using the AGREE (Appraisal of Guidelines, Research and Evaluation in Europe) instrument. Results: Thirty-three, 32, and 18 relevant documents for cervical, breast, and colorectal cancer, respectively, were identified. Only some documents (19, 12 and 13 for cervical, breast, and colorectal cancer, respectively) could be evaluated with AGREE. Items included in the domain “scope and purpose” obtained the highest scores, followed by “clarity of presentation” domain, while “applicability”, “patient involvement,” and “conflict of interest disclosure” domains obtained the lowest scores. The quality did not improve in more recent documents. Documents produced by governmental agencies, on average, had higher scores than documents by scientific societies, particularly for “stakeholder involvement” and “applicability”. Conclusions: Documents from different countries and health systems differ in terms of the main recommendations given and in the quality of the documents. Those produced by governmental agencies have a more multidisciplinary authorship and pay more attention to applicability than do those produced by scientific societies.